2018
DOI: 10.1037/xlm0000530
|View full text |Cite
|
Sign up to set email alerts
|

Mood state dissociates conflict adaptation within tasks and across tasks.

Abstract: The present study investigated the influence of mood state (positive vs. negative) on the cognitive control process of conflict adaptation. A task-switching paradigm was applied, allowing to assess conflict adaptation both within tasks and across tasks. A success-failure manipulation was applied for mood induction. Within-task conflict adaptation tended to be larger in negative mood than in positive mood, in line with previous findings in the literature. Across-task conflict adaptation was also observed, but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
5
1
Order By: Relevance
“…Besides the stimulusdriven disruptive effect of unpleasant stimuli on cognitive control adjustments (Padmala et al, 2011), control adaptations seem to also be dependent on one's emotional state. Some studies suggest that unpleasant affective states will prioritize conflict processing, which will strengthen cognitive control adjustments (e.g., van Steenbergen et al, 2010;Schuch and Pütz, 2018). Although we cannot discard the possible influences of emotional states on control adjustments in our study, we found electrophysiological evidence that the influence of the previous trial WM load on distracter processing is absent (i.e., there is no control adaptation) when the distracter presents unpleasant content.…”
Section: Adjustments In Cognitive Control May Be Reduced During An Uncontrasting
confidence: 47%
“…Besides the stimulusdriven disruptive effect of unpleasant stimuli on cognitive control adjustments (Padmala et al, 2011), control adaptations seem to also be dependent on one's emotional state. Some studies suggest that unpleasant affective states will prioritize conflict processing, which will strengthen cognitive control adjustments (e.g., van Steenbergen et al, 2010;Schuch and Pütz, 2018). Although we cannot discard the possible influences of emotional states on control adjustments in our study, we found electrophysiological evidence that the influence of the previous trial WM load on distracter processing is absent (i.e., there is no control adaptation) when the distracter presents unpleasant content.…”
Section: Adjustments In Cognitive Control May Be Reduced During An Uncontrasting
confidence: 47%
“…Experimental evidence for the affect ► control link Many studies have reported an affective modulation of control by tonic affect. These studies induced mood states with movie clips (Schuch & Koch, 2015), music and imagination (van Steenbergen, Band, & Hommel, 2010), cartoons (van Steenbergen, Band, Hommel, Rombouts, & Nieuwenhuis, 2015, approach/avoidance gestures (Hengstler, Holland, van Steenbergen, & van Knippenberg, 2014), mock feedback on either intelligence tests (Schuch & Pütz, 2018;Schuch, Zweerings, Hirsch, & Koch, 2017) or task performance (Yang & Pourtois, 2018), or particular screen colors (X. Wang, Zhao, Xue, & Chen, 2016).…”
Section: Conflict-triggered Affect Drives Control Adaptation-the Affementioning
confidence: 99%
“…Apart from response-selection bottleneck models that predict a PRP effect only in the RT (e.g., Pashler, 1994), dual-task models, such as the capacity sharing model (Tombu & Jolicoeur, 2003) and the ECTVA model (Logan & Gordon, 2001), can account for SOA effects in RTs and error rates, thus justifying the use of integrated measures. Moreover, integrated measures have already been used in the task-switching domain (e.g., Draheim, Hicks, & Engle, 2016;Schuch & Pütz, 2018) and the dual-task domain (Han & Marois, 2013;Kunde, Pfister, & Janczyk, 2012).…”
Section: Use Of Integrated Speed-accuracy Measuresmentioning
confidence: 99%